Magnetic hydrated calcium silicate microcrystalline cellulose nano-microsphere as well as preparation method and application thereof
Through ultrasonic treatment and modification of sodium hydroxide, urea and other solutions, magnetic hydrated calcium silicate microcrystalline cellulose nano microspheres were prepared, which solved the problem of difficulty in separation of hydrated calcium silicate after adsorption of heavy metals, and achieved efficient adsorption and easy separation.
Patent Information
- Application Number
- CN202510002163.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-21
AI Technical Summary
The existing hydrated calcium silicate materials have difficulty in separation after adsorbing heavy metals and have poor mechanical strength, which restricts their development in the field of adsorption.
Ultrasonic treatment was used to combine sodium hydroxide, urea and water with mixed solution, modified microcrystalline cellulose and magnetic hydrated calcium silicate nanoparticles, and magnetic hydrated calcium silicate microcrystalline cellulose nanometers were prepared by cross-linking reaction.
It improves the adsorption efficiency and separation efficiency of heavy metals, has stable material form, easy separation, and has a wide range of application prospects.
Smart Images

Figure CN119657097A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and specifically relates to magnetic calcium silicate hydrate microcrystalline cellulose nanospheres and a preparation method and application thereof. Background Art
[0002] At the current stage, a large number of methods have been developed and promoted to treat heavy metals and antibiotics. The mainstream methods include chemical binding, adsorption, photocatalysis, membrane separation, microbial treatment, ion exchange, etc. Among these many methods, adsorption has become the main method for treating heavy metal ions in industrial production due to its advantages of low production cost, simple operation, no secondary pollution to the environment, and wide adaptability. The adsorption method can be roughly divided into three methods in the adsorption process, including chemical adsorption, physical adsorption, and biological adsorption. The photocatalytic degradation method has become a hot research direction for catalytic degradation of TCH in recent years due to its advantages of simple operation, high selection efficiency, and environmental friendliness. Therefore, combining the above advantages, it has an important research method in the adsorption of heavy metal ions and the degradation of TCH, and is considered to be a very promising method for removing heavy metal ions and degrading organic matter.
[0003] At present, calcium silicate hydrate is widely studied as an environmentally friendly adsorbent that can be used to adsorb heavy metal ions without causing pollution to the environment. However, due to its poor mechanical strength and its amorphous and easy loss, it is difficult to separate it from pollutants in the water, which restricts the development of calcium silicate hydrate in the adsorption field.
[0004] The Chinese invention patent with publication number CN108043356A discloses a magnetic core-shell porous calcium silicate material and its preparation method. The method uses acetaldehyde as a reducing agent, ethylene glycol as a solvent, and polyethylene glycol and polyvinyl pyrrolidone as a template and dispersant. With the participation of acetate, trivalent iron salt is reduced to obtain spherical ferroferric oxide with uniform particle size and complete particles; then the obtained spherical ferroferric oxide is directly dispersed in anhydrous ethanol, and silicate and calcium salt are used as raw materials to in-situ synthesize and directly coat porous calcium silicate on the surface of ferroferric oxide particles; finally, ultrasonic dispersion and mechanical stirring are used to separate the unstable and overly thick calcium silicate coated on the particle surface, and a core-shell porous calcium silicate material (Fe 2 O 4 ) with uniform and stable calcium silicate coating is obtained. 3 O 4 @CaSiO 3 ). This invention overcomes the problem that porous calcium silicate is complicated to separate after adsorbing heavy metals and cannot be operated continuously, and can realize continuous operation of adsorption and separation. However, it has few contact sites with heavy metals and there are also problems such as poor stability of calcium silicate coating.
[0005] In order to solve the problem of poor stability of calcium silicate coating, the Chinese invention patent with publication number CN115055171A provides a composite magnetic adsorption material and its preparation method and use. By using magnetic ferroferric oxide microspheres as the core, polydopamine (PDA) as the middle layer, and calcium silicate hydrate (CSH) as the surface adsorption molecular chain, a high-performance Fe 3 O 4 @PDA@CSH composite magnetic adsorption material. Similarly, the Chinese invention patent with publication number CN108043357A uses magnetic ferroferric oxide as the core, first coats the surface with silicon dioxide, which has good stability in the processing environment, and then coats the surface of silicon dioxide with porous calcium silicate to form a single-core double-shell structure material, recorded as Fe 3 O 4 @SiO 2 @CaSiO 3 Although the introduction of the intermediate layer strengthens the connection between the core and the shell and improves the stability of the material, it hinders the reduction of the particle size. The particle size of the obtained material is usually large, which is not conducive to the optimization of the specific surface area. In addition, the introduction of additional preparation processes is also likely to increase the complexity of the process, making it difficult to apply on a large scale.
[0006] The Chinese invention patent with publication number CN110681361A provides a method for preparing magnetic cellulose microspheres with a core-shell structure and its application. 3 O 4 Magnetic core; Silane coupling agent modified magnetic cellulose obtained by in-situ composite method; Carboxyl modified magnetic cellulose microspheres obtained by reaction with diethylenetriaminepentaacetic acid. Amino groups were grafted on the cellulose surface by using silane coupling agent, and then carboxyl groups were chemically modified by amidation reaction to obtain Fe 3 O 4 The core-shell structure of the magnetic core can not only achieve rapid separation and reuse under the action of an external magnetic field, but also increase the specific surface area of the adsorbent. However, the amidation process is relatively cumbersome, firstly, it is necessary to use a silane coupling agent to graft and introduce amino groups, and then complete the carboxyl modification through an amidation reaction.
[0007] Considering the narrow applicability of a single adsorption component and structure, there is still much room for improvement in adsorption performance. How to combine different structures through a simple preparation process to form core-shell magnetic adsorption particles with excellent performance and multiple adsorption sites still faces various challenges such as material selection, design and process. Summary of the invention
[0008] In view of the above-mentioned defects of the prior art, in the first aspect of the present invention, a method for preparing magnetic calcium silicate hydrate microcrystalline cellulose nanospheres with a simple process is provided, comprising the following steps: S1, Fe3 O 4 Nanoparticles and calcium silicate hydrate (CSH) were added to water and subjected to ultrasonic treatment. After completion, the product was collected and purified to obtain magnetic calcium silicate hydrate nanoparticles (Fe 3 O 4 / CSH); S2, mixing sodium hydroxide, urea and water to form a mixed solution; adding microcrystalline cellulose (MCC) to the mixed solution, and mixing to obtain a microcrystalline cellulose suspension; S3, mixing the magnetic calcium silicate hydrate nanoparticles and microcrystalline cellulose suspension to obtain a gel solution; then adding a calcium chloride aqueous solution to the gel solution for cross-linking, and after completion, collecting and purifying the product to obtain magnetic calcium silicate hydrate microcrystalline cellulose nanospheres (Fe 3 O 4 / CSH@MCC).
[0009] Preferably, in the S1, Fe 3 O 4 The nanoparticles were prepared by a coprecipitation method, which includes the following steps: mixing an ethylene glycol solution of an iron salt with sodium acetate, reacting under high pressure at 195-205 °C for 9-11 h, collecting and purifying the product after completion, and obtaining Fe 3 O 4 Nanoparticles.
[0010] Further preferably, the ethylene glycol solution of iron salt is composed of 1.15-1.25 g FeCl 3 6H 2 O is dissolved in 39.50-40.50mL of ethylene glycol; the amount of sodium acetate is 3.15-3.25 g Preferably, in S1, the calcium silicate hydrate is prepared by a solid phase method, which comprises the following steps: mixing sodium metasilicate nonahydrate with calcium chloride and grinding until the mixture is in a thin mortar state and solidified into a sheet state, and after completion, collecting and purifying the product to obtain calcium silicate hydrate.
[0011] Further preferably, the molar ratio of the sodium metasilicate nonahydrate to calcium chloride is 1:0.9-1.1.
[0012] The present invention can adopt the existing Fe 3 O 4 Nanoparticles and hydrated calcium silicate can be prepared, or the above raw materials can be obtained by homemade methods. Among them, the coprecipitation method is a relatively simple and easy-to-operate technology that does not require complex instruments and equipment. 3 O 4Nanoparticles have high purity and crystallinity, and show good chemical reactivity. For calcium silicate hydrate, the solid phase method is suitable. It has the significant advantages of easy availability of raw materials, mild preparation conditions and simple operation, avoiding the pre-treatment operation of many toxic and harmful reagents, and the yield of calcium silicate hydrate obtained is high.
[0013] Preferably, in the S1, Fe 3 O 4 The mass ratio of the nanoparticles to the hydrated calcium silicate is 1:1.5-2.0.
[0014] Water is used as a dispersion medium in the step to promote dispersion and create a suitable environment for the reaction. As shown in the example, 1.0 g Fe 3 O 4 10 mL of water can be added to the nanoparticles. Other amounts can also achieve the purpose of this step. Those skilled in the art can select the amount of water according to the actual production scale.
[0015] Preferably, in S2, the mass ratio of sodium hydroxide, urea and water is 6.5-7.5:11.0-12.5:80.5-81.5.
[0016] In Fe 3 O 4 In the preparation of / CSH@MCC, sodium metasilicate nonahydrate, anhydrous calcium chloride and Fe 3 O 4 The formula ratio of nanoparticles is obtained based on theoretical calculations, and a better binding effect can be achieved at this ratio. In addition, the weight ratio of sodium hydroxide, urea, and water is 7:12:81, which is the best ratio for dissolving microcrystalline cellulose, which can save raw materials and improve dissolution efficiency. This ratio is effective in improving Fe 3 O 4 The encapsulation of / CSH has an auxiliary effect and does not play an absolute role in the adsorption.
[0017] Preferably, in S2, based on the mixed solution dosage of 100 mL, 1.95-2.05 g of microcrystalline cellulose is added and mixed to obtain a microcrystalline cellulose suspension.
[0018] Preferably, in S3, the mass ratio of the magnetic calcium silicate hydrate nanoparticles to the microcrystalline cellulose in the microcrystalline cellulose suspension is 3:2.0-4.5.
[0019] Preferably, in S3, based on the amount of gel solution used being 100 mL, 9.50-10.50 mL of calcium chloride aqueous solution is added correspondingly; the concentration of the calcium chloride aqueous solution is 4.95 wt.%-5.05 wt.%.
[0020] In the second aspect of the present invention, a magnetic calcium silicate hydrate microcrystalline cellulose nanosphere is provided, which has a wide coverage of water bodies, high adsorption efficiency for heavy metals, and is easy to separate. The nanosphere is prepared by the preparation method provided by the first aspect of the present invention.
[0021] Preferably, the particle size of the magnetic calcium silicate hydrate microcrystalline cellulose nanospheres is 50-150 nm and the density is 0.5-0.7 g / cm 3 .
[0022] In the third aspect of the present invention, there is provided an application of the magnetic calcium silicate hydrate microcrystalline cellulose nanospheres according to the second aspect of the present invention, specifically, using the nanospheres to adsorb heavy metal ions or catalyze the degradation of organic matter.
[0023] In the magnetic calcium silicate hydrate microcrystalline cellulose nanospheres, calcium silicate hydrate and ferroferric oxide are electronegatively bonded to form a core-shell structure carrying magnetism, and the magnetic calcium silicate hydrate nanoparticles are coated with modified microcrystalline cellulose. The invention can improve the adsorption effect of heavy metal ions in water, and is convenient for itself to be separated from the water and used as a catalyst for catalytic degradation of organic matter.
[0024] Based on the above technical solutions, the design concept and principle of the present invention are as follows: Fe 3 O 4 / CSH intermediate product preparation, the introduction of ferroferric oxide for loading solves the problems of difficult recovery and easy loss after adsorption. 3 O 4 The binding process of the intermediate product of / CSH is a physical electronegativity binding method in an ultrasonic environment. This method does not require any reagents for pre-treatment, and can achieve a high degree of binding. 3 O 4 The diameter of the loaded morphology is kept within 100 nm on average, and its huge specific area is beneficial to the adsorption process.
[0025] The present invention utilizes the property that microcrystalline cellulose itself is insoluble in water, and uses a mixed solution made of sodium hydroxide, urea, and water to increase the expansion and dissolution of microcrystalline cellulose chains. In this process, not only adsorption groups (such as amino groups, etc.) are introduced, but also the purpose of achieving a cross-linking effect is achieved. This design can strengthen Fe without the need for additional preparation of a binding layer. 3 O 4 / CSH morphology is fixed, combined with microcrystalline cellulose and its groups to achieve multiple adsorption effects. 3 O 4 The average diameter of / CSH@MCC remained at about 150 nm, and the adsorption specific area was further increased.
[0026] As described above, the present invention, by arranging a magnetic nano core in the calcium silicate hydrate, improves the overall density and the coverage of the water body on the one hand, and can collect the rice microspheres dispersed in the water body through the magnetism of the magnetic nano core, thereby improving the adsorption efficiency of heavy metals and the efficiency of separation from the water body under the combined effect. Secondly, the specific surface area of the prepared calcium silicate hydrate nano microspheres is improved by selecting a nano-scale magnetic nano core, and the contact area of the magnetic calcium silicate hydrate microcrystalline cellulose nano microspheres with heavy metal ions when dispersed in the water body is further improved, thereby further improving the adsorption efficiency of heavy metals. The cellulose chain expansion and dissolution technology carries out amino modification on microcrystalline cellulose, further increases the amino groups on the microcrystalline cellulose, and introduces other heavy metal adsorption groups at the same time. Under the combined effect, the adsorption effect and adsorption capacity of a single magnetic calcium silicate hydrate microcrystalline cellulose nanoparticle on heavy metals are improved.
[0027] Overall, Fe 3 O 4 / CSH@MCC has the following significant advantages during its preparation: basically no toxic or harmful reagents are involved in the synthesis and preparation, and the raw materials used are low-cost and easy to obtain. The entire preparation process has low difficulty in operation and high industrial production replicability.
[0028] Compared with the prior art, the present invention has the following advantages and beneficial effects: The present invention provides a method for preparing magnetic calcium silicate hydrate microcrystalline cellulose nanospheres, which utilizes cellulose chain expansion and dissolution to achieve the purpose of modification and optimization of binding degree, reduces the complicated binding layer preparation process, and has the advantages of wide raw material sources, simple process, low operation difficulty, high industrial production replicability, etc.
[0029] The invention provides a magnetic calcium silicate hydrate microcrystalline cellulose nanosphere. The material has a stable shape, a wide coverage range of water bodies, high adsorption efficiency for heavy metals, and is easy to separate.
[0030] The invention provides an application of magnetic calcium silicate hydrate microcrystalline cellulose nanospheres, which have broad application prospects as adsorption materials in adsorbing heavy metal ions or catalytically degrading organic matter. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 is a scanning electron microscope image of the magnetic calcium silicate hydrate microcrystalline cellulose nanospheres prepared in Example 1; Figure 2 is the infrared spectrum diffraction pattern of the calcium silicate hydrate, the magnetic calcium silicate hydrate nanoparticles, and the magnetic calcium silicate hydrate microcrystalline cellulose nanospheres in Example 1; Figure 3It is a wide-angle X-ray diffraction pattern of the calcium silicate hydrate, the magnetic calcium silicate hydrate nanoparticles, and the magnetic calcium silicate hydrate microcrystalline cellulose nanospheres in Example 1; Figure 4 The magnetic calcium silicate hydrate microcrystalline cellulose nanospheres prepared in Example 1 adsorb lead ions (Pb 2+ )、nickel ion(Ni 2+ ), copper ions (Cu 2+ )、Silver ions(Ag + )’s adsorption kinetics diagram; Figure 5 The magnetic calcium silicate hydrate microcrystalline cellulose nanospheres prepared in Example 1 adsorb lead ions (Pb 2+ )、nickel ion(Ni 2+ ), copper ions (Cu 2+ ) of the adsorption isotherm.
[0032] Figure 6 The magnetic calcium silicate hydrate microcrystalline cellulose nanospheres prepared in Example 1 adsorb lead ions (Pb 2+ )、nickel ion(Ni 2+ )), copper ions (Cu 2+ ) and silver ions (Ag + ) and extract the adsorption kinetics for photocatalytic degradation of tetracycline hydrochloride; Figure 7 It is the principle diagram of the synthesis of heavy metals in magnetic hydrated calcium silicate microcrystalline cellulose nanospheres; Figure 8 This is a schematic diagram of the heavy metal adsorption principle of magnetic calcium silicate hydrate microcrystalline cellulose nanospheres. DETAILED DESCRIPTION
[0033] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0034] Example 1 The preparation method of magnetic hydrated calcium silicate microcrystalline cellulose nanospheres comprises the following steps: S1, 1.2 g of FeCl 3 6H 2 O was dissolved in 40 mL of ethylene glycol, 3.2 g of sodium acetate was slowly added under stirring, stirred evenly, and reacted in a high-pressure reactor at 200 °C for 10 h. After the reaction was completed, it was collected by a magnet and vacuum dried at 60 °C for 10 h to obtain Fe 3 O 4 Nanoparticles; Accurately weigh 0.01 mol of sodium metasilicate nonahydrate and 0.01 mol of calcium chloride in different mortars, with a calcium-silicon molar ratio of Ca:Si≈1:1, and grind them into powders in mortars for 5 min, then mix the two in a mortar and grind them thoroughly for about 15 min. During the mixed grinding process of sodium metasilicate nonahydrate and calcium chloride, the state changes from powder to precipitation of water to thin mortar to solidification into flakes, and the by-products are washed with water; finally, the white solid is dried in a constant temperature blast drying oven at 60 °C for 4 h and then ground into powder to obtain powdered calcium silicate hydrate; 2.00 g hydrated calcium silicate powder, 1.00 g Fe 3 O 4 The nanoparticles were placed in a beaker and 10 mL of deionized water was added to mix with each other, and then ultrasonicated for 1 h to allow the two to mix with each other and be evenly dispersed in the solution. After completion, the product was collected and purified to obtain magnetic hydrated calcium silicate; S2, prepare 100 mL of a mixed solution of an alkali / urea system (the mass ratio of NaOH:urea:water is 7:12:81), place it on a magnetic stirrer, adjust it to a suitable speed, accurately weigh 2.00 g of microcrystalline cellulose, slowly add it to the above solution, and stir at room temperature for 2 h to form a uniform milky white microcrystalline cellulose suspension; S3, 3.0 g of magnetic calcium silicate hydrate and 2.0 g of microcrystalline cellulose suspension were uniformly mixed to form a gel solution. After aging for 24 h, the remaining bubbles were removed and 5 wt.% CaCl was added to the solution using a rubber dropper. 2 The solution was used to crosslink 100.00 mL of gel. After completion, the product was collected and purified to obtain magnetic calcium silicate hydrate microcrystalline cellulose nanospheres (Fe 3 O 4 / CSH@MCC).
[0035] The average particle size of the magnetic calcium silicate hydrate microcrystalline cellulose nanospheres of this embodiment was measured by reference to GB / T 32499-2016 and the density was measured by GB / T 5162-2021. The result was 50 nm and the density was 0.59 g / cm 3 .
[0036] Example 2 Process stability is the basis of product quality stability. This example repeats the preparation process of Example 1 to produce different batches of products, and obtains (1) an average particle size of 45 nm and a density of 0.62 g / cm 3 ; (2) Average particle size: 42 nm, density: 0.62 g / cm 3The method of the present invention has good process stability and reproducibility, the obtained product has high consistency, reduces the fluctuation range, and improves the reliability and service life of the product.
[0037] Example 3 This example characterizes the morphological structure of the magnetic calcium silicate hydrate microcrystalline cellulose nanospheres prepared in Example 1. The magnetic calcium silicate hydrate microcrystalline cellulose nanospheres were observed by scanning electron microscopy imaging. The results are as follows: Figure 1 The calcium silicate hydrate, magnetic calcium silicate hydrate nanoparticles and magnetic calcium silicate hydrate microcrystalline cellulose nanospheres in Example 1 were characterized by infrared spectroscopy and X-ray diffraction. The results are shown in order. Figure 2 , 3 shown.
[0038] like Figure 1 As shown in the SEM image, Fe 3 O 4 Combined with the electronegativity of calcium silicate hydrate, microcrystalline cellulose encapsulated the magnetic calcium silicate hydrate, indicating that the prepared magnetic calcium silicate hydrate microcrystalline cellulose nanospheres formed a core-shell structure. Some particles were observed to aggregate due to cross-linking, and the particles were larger than 150 nm, but the average particle size was still within the target range.
[0039] like Figure 2 As shown in the spectrum of CSH, the wavelength at 1640 cm -1 The bending vibration peak of HOH and -OH is 950 cm -1 is the stretching vibration peak of v(Si-O)Q2, 665 cm -1 The nearby peaks are the bending vibration peaks of Si-O-Si, 1450-1485 cm -1 It is the characteristic absorption peak of CaO and the stretching peak of carbonate. 3 O 4 / CSH spectrum in Fe 3 O 4 There is a 584 cm -1 The results show that Fe 3 O 4 and CSH have been combined. 3 O 4 In the spectrum of / CSH@MCC, 1630 cm -1 is the deformation vibration peak of C=C and NH bond, 1430 cm -1 is the deformation vibration peak of secondary amine, confirming that MCC and Fe 3 O 4 / CSH functionalization combination.
[0040] like Figure 3 As shown, the reflection peaks in the X-ray diffraction patterns of calcium silicate hydrate, magnetic calcium silicate hydrate nanoparticles and magnetic calcium silicate hydrate microcrystalline cellulose nanospheres all have Fe 3 O 4 Characteristics of nanoparticles, including Fe 3 O 4 The characteristics of the nanoparticles are: 8.26°, 30.02°, 35.40°, 43°, 53.36°, 56.9°, 62.5°, the characteristics of the CSH nanoparticles are: 31.8°, 45.5°, with a planar distribution, and CSH and Fe 3 O 4 The above characteristics of / CSH, the diffraction peak at 2.82° changes from a single peak to a double peak, which is the characteristic peak of cellulose II crystal form, indicating that Fe 3 O 4 Combined with CSH, Fe 3 O 4 / CSH is covered by MCC.
[0041] Example 4 This example is an application example of magnetic calcium silicate hydrate microcrystalline cellulose nanospheres for adsorbing heavy metal ions. The magnetic calcium silicate hydrate microcrystalline cellulose nanospheres prepared in Example 1 are added to lead ions (Pb 2+ )、nickel ion(Ni 2+ ), copper ions (Cu 2+ )、Silver ions(Ag + ) in heavy metal solutions with an initial concentration of 200 mg / L, separation was performed after a reaction time of 10-480 min and separation was performed after a reaction time of 60 min at different adsorbate concentrations of 20-800 mg / L to determine the lead ion (Pb 2+ )、nickel ion(Ni 2+ ), copper ions (Cu 2+ )、Silver ions(Ag + ) concentration, calculate the lead ion (Pb 2+ )、nickel ion(Ni 2+ ), copper ions (Cu 2+ )、Silver ions(Ag + ) and the results are shown in Tables 1 and 2.
[0042] Table 1: Changes in concentration and adsorption rate of heavy metal ions after adsorption as a function of reaction time
[0043] Table 2: Changes in the concentration and adsorption rate of heavy metal ions after adsorption as a function of adsorbate concentration
[0044] Referring to Tables 1 and 2, Fe in Example 1 3 O 4 The absorption rate of lead ions, nickel ions, copper ions and silver ions by / CSH@MCC reached 97.19%, 99.53%, 86.32% and 48.18%, respectively. Before the reaction time reached 60 min, the concentration (mg / L) after adsorption gradually decreased. After the reaction time reached 60 min, the concentration (mg / L) after adsorption remained basically unchanged. At this time, Fe 3 O 4 The adsorption of lead ions by / CSH@MCC reached a maximum and presented a dynamic equilibrium. After the reaction time reached 60 min, the concentration after adsorption fluctuated slightly. Analysis showed that the fluctuation of the concentration after adsorption was caused by errors in the detection process after the reaction time reached 60 min.
[0045] The obtained data were processed to investigate the adsorption of lead ions (Pb 2+ )、nickel ion(Ni 2+ ), copper ions (Cu 2+ )、Silver ions(Ag + The adsorption kinetics of ) was studied, and the obtained parameters are shown in Table 3. The corresponding adsorption kinetics diagram is shown in Figure 4 shown.
[0046] Table 3: Adsorption kinetic parameters
[0047] The above results show that the correlation coefficient (R 2 ) is higher, showing better compliance to adsorption, where the pseudo-second-order kinetic model is fitted as follows Figure 4 Therefore, chemical adsorption is the rate-controlling step in the adsorption process.
[0048] Figure 5 is the Fe of Example 1 3 O 4 / CSH@MCC for lead ions (Pb 2+ )、nickel ion(Ni 2+ ), copper ions (Cu 2+ ) are fitted to the Langmuir (a), Freundlich (b) and Temkin (c) isotherms of adsorption. The isotherm parameters are shown in Table 4.
[0049] Table 4: Isotherm parameters
[0050] The above results show that the correlation coefficients of the isotherm parameters of the Langmuir model are all greater than 0.993, and the Langmuir isotherms are well fitted, indicating that the Fe 3 O 4 The active sites on the / CSH@MCC surface may have monolayer adsorption characteristics.
[0051] Example 5 This example is an application example of magnetic calcium silicate hydrate microcrystalline cellulose nanospheres for catalytic degradation of organic matter. The magnetic calcium silicate hydrate microcrystalline cellulose nanospheres prepared in Example 1 are added to lead ions (Pb 2+ )、nickel ion(Ni 2+ ), copper ions (Cu 2+ )、Silver ions(Ag + ) After adsorption, the adsorbent is filtered, washed, dried, classified and stored for later use, to obtain the adsorbed product and the Fe 3 O 4 / CSH@MCC@Pb、Fe 3 O 4 / CSH@MCC@Cu、Fe 3 O 4 / CSH@MCC@Ni、Fe 3 O 4 / CSH@MCC@Ag and Fe 3 O 4 / CSH@MCC. It was used as a catalyst for photocatalytic degradation of tetracycline hydrochloride. After photocatalytic degradation of tetracycline hydrochloride by 400W-LED light source, the degradation rate of tetracycline hydrochloride in the solution was measured. The results are shown in Table 5.
[0052] Table 5: Degradation test results of tetracycline hydrochloride
[0053] The data were processed to obtain the adsorption kinetics diagram of tetracycline hydrochloride degradation. Figure 6 The Fe prepared in Example 1 3 O 4 / CSH@MC and Fe extracted after adsorption 3 O 4 / CSH@MCC@Pb、Fe 3 O 4 / CSH@MCC@Cu、Fe 3 O 4 / CSH@MCC@Ni and Fe 3 O 4 / CSH@MCC@Ag was used as a catalyst for photocatalytic degradation of tetracycline hydrochloride and the adsorption kinetics test results of photocatalytic tetracycline hydrochloride.
[0054] The parameters obtained based on the above results are as follows and shown in Table 6 for the pseudo-first-order kinetic model.
[0055] Table 6: Pseudo-first-order kinetic model
[0056] The results showed that the relevant linear relationships were all greater than 0.98, indicating that the catalytic degradation reaction conformed to the pseudo-first-order kinetic model.
[0057] Based on the above research results, the principle diagram of the synthesis of heavy metals in magnetic calcium silicate hydrate microcrystalline cellulose nanospheres is as follows Figure 7 The adsorption principle diagram is shown in Figure 8 As shown. The present invention utilizes the property that microcrystalline cellulose itself is insoluble in water, and uses a mixed solution made of sodium hydroxide, urea, and water to increase the expansion and dissolution of microcrystalline cellulose chains. In this process, not only adsorption groups (such as amino groups, etc.) are introduced, but also the purpose of achieving a cross-linking effect is achieved. This design can strengthen Fe without additional preparation of a binding layer. 3 O 4 The fixation of the morphology of / CSH and the combination of microcrystalline cellulose and its groups achieve the effect of multiple adsorption.
[0058] The present invention, by arranging a magnetic nano core in the calcium silicate hydrate, improves the overall density and the coverage of the water body on the one hand, and can collect the rice microspheres dispersed in the water body through the magnetism of the magnetic nano core, thereby improving the adsorption efficiency of heavy metals and the efficiency of separation from the water body under the comprehensive effect. Secondly, by selecting the nano-scale magnetic nano core, the specific surface area of the prepared calcium silicate hydrate nano microspheres is increased, and the contact area of the magnetic calcium silicate hydrate microcrystalline cellulose nano microspheres with heavy metal ions when dispersed in the water body is further increased, thereby further improving the adsorption efficiency of heavy metals. The cellulose chain expansion and dissolution technology is used to amino-modify the microcrystalline cellulose, further increasing the amino groups on the microcrystalline cellulose, and introducing other heavy metal adsorption groups at the same time. Under the comprehensive effect, the adsorption effect and adsorption capacity of the single magnetic calcium silicate hydrate microcrystalline cellulose nanoparticles on heavy metals are improved. As an adsorbent material, it has broad application prospects in adsorbing heavy metal ions or catalytic degradation of organic matter.
[0059] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for preparing magnetic calcium silicate hydrate microcrystalline cellulose nanospheres, characterized in that: The steps include: S1, adding Fe3O4 nanoparticles and hydrated calcium silicate to water, and performing ultrasonic treatment; after completion, collecting and purifying the product to obtain magnetic hydrated calcium silicate nanoparticles; S2, mixing sodium hydroxide, urea and water to form a mixed solution; adding microcrystalline cellulose to the mixed solution, and mixing to obtain a microcrystalline cellulose suspension; S3, mixing the magnetic calcium silicate hydrate nanoparticles and microcrystalline cellulose suspension to obtain a gel solution; then adding a calcium chloride aqueous solution thereto for cross-linking, and after completion, collecting and purifying the product to obtain magnetic calcium silicate hydrate microcrystalline cellulose nanospheres.
2. The method for preparing magnetic calcium silicate hydrate microcrystalline cellulose nanospheres according to claim 1, characterized in that: In S1, the Fe3O4 nanoparticles are prepared by a coprecipitation method, which includes the following steps: mixing an ethylene glycol solution of an iron salt with sodium acetate, reacting under high pressure at 195-205°C for 9-11 hours, and collecting and purifying the product to obtain Fe3O4 nanoparticles.
3. The method for preparing magnetic calcium silicate hydrate microcrystalline cellulose nanospheres according to claim 1, characterized in that: In S1, calcium silicate hydrate is prepared by a solid phase method, which comprises the following steps: mixing sodium metasilicate nonahydrate with calcium chloride and grinding until it is in a thin mortar state and solidified into a sheet state, and after completion, the product is collected and purified to obtain calcium silicate hydrate.
4. The method for preparing magnetic calcium silicate hydrate microcrystalline cellulose nanospheres according to claim 1, characterized in that: In the S1, the mass ratio of Fe3O4 nanoparticles to calcium silicate hydrate is 1:1.5-2.
0.
5. The method for preparing magnetic calcium silicate hydrate microcrystalline cellulose nanospheres according to claim 1, characterized in that: In the S2, the mass ratio of sodium hydroxide, urea and water is 6.5-7.5:11.0-12.5:80.5-81.5; based on the amount of the mixed solution being 100 mL, 1.95-2.05 g of microcrystalline cellulose is added and mixed to obtain a microcrystalline cellulose suspension.
6. The method for preparing magnetic calcium silicate hydrate microcrystalline cellulose nanospheres according to claim 1, characterized in that: In S3, the mass ratio of the magnetic calcium silicate hydrate nanoparticles to the microcrystalline cellulose in the microcrystalline cellulose suspension is 3:2.0-4.
5.
7. The method for preparing magnetic calcium silicate hydrate microcrystalline cellulose nanospheres according to claim 1, characterized in that: In S3, based on the amount of gel solution used being 100 mL, 9.50-10.50 mL of calcium chloride aqueous solution is added; the concentration of the calcium chloride aqueous solution is 4.95 wt.%-5.05 wt.%.
8. A magnetic calcium silicate hydrate microcrystalline cellulose nanosphere, characterized in that: The method is prepared according to any one of claims 1 to 7.
9. The magnetic calcium silicate hydrate microcrystalline cellulose nanospheres according to claim 8, characterized in that: The particle size of the magnetic calcium silicate hydrate microcrystalline cellulose nanospheres is 50-150 nm and the density is 0.5-0.7 g / cm 3 .
10. An application of the magnetic calcium silicate hydrate microcrystalline cellulose nanospheres as claimed in claim 8 or 9, characterized in that: Used to adsorb heavy metal ions or catalytically degrade organic matter.
Citation Information
Patent Citations
Magnetic core-shell type porous Calcium silicate material and preparation method thereof
CN108043356A
Magnetic single-core double-shell type porous calcium silicate material and preparation method thereof
CN108043357A
Preparation method and application of magnetic cellulose microspheres with core-shell structure
CN110681361A
Composite magnetic adsorption material as well as preparation method and application thereof
CN115055171A